Cover Picture. Issue 4 (21st December 2021) - Unknown
Abstract : This cover image is based on the Review Hypoxia adaptation in the cornea: Current animal models and underlying mechanisms by Kunpeng Pang, Anton Lennikov, Menglu Yang. https://doi.org/10.1002/ame2.12192 . This review introduced the pathology of cornea under hypoxia and the mechanism of hypoxia adaptation by the activation of hypoxia inducible factor (HIF) signalling pathway, to discuss the current animal models used in this field and future research direction.